2017
DOI: 10.18240/ijo.2017.04.10
|View full text |Cite
|
Sign up to set email alerts
|

Soluble expression of recomb inant cMyc, Klf4, Oct4, and Sox2 proteins in bacteria and transduction into living cells

Abstract: The results in the present study indicate the four important reprogramming proteins, cMyc, Klf4, Oct4, and Sox2, can be produced in soluble format in bacteria with low cost. Our new method thus might be expected to greatly contribute to the future study of iPSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Recombinant Oct4 proteins were produced in mammalian cells [ 18 ], insect cells [ 19 ], yeast [ 20 ], and E. coli . [ 21 ]. Although some reports do evaluate their protein yields, various units were used.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recombinant Oct4 proteins were produced in mammalian cells [ 18 ], insect cells [ 19 ], yeast [ 20 ], and E. coli . [ 21 ]. Although some reports do evaluate their protein yields, various units were used.…”
Section: Resultsmentioning
confidence: 99%
“…Although some reports do evaluate their protein yields, various units were used. The yield from previous studies in insect cells and yeast showed that the recombinant Oct4 yield was 6.1 mg/L [ 19 ] and 210 mg/L [ 21 ], respectively. Our present study indicates that the yield of rhOct4 was approximately 0.41% of the total soluble proteins.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations